SATISFACTION ANALYSIS OF RESPONSIVE WEB DESIGN (RWD) USING PIECES METHOD IN YOBAGI: TECHNOLOGY PLATFORM BASED ON SOCIALPRENEURSHIP - Dwi Yuny Sylfania; Rendy Rian Chrisna Putra; Fransiskus Panca Juniawan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
The Covid-19 pandemic has had a huge impact on society. There have been layoffs for some people, which will have an impact on their economy, which is getting worse. Another impact was felt by MSMEs where their transactions also decreased. Yobagi is proposed to overcome this problem by becoming a social entrepreneurship-based media platform that becomes an intermediary media for anyone who has the desire to share their skills, knowledge, and experiences. Yobagi is also a marketplace for MSMEs to promote their products or services. The purpose of this research is for people to improve their skills, be able to innovate, so they can run new businesses to improve their economy. Likewise, MSMEs have increased their transactions. The research uses the prototype method which consists of five stages, namely Communication, Quick Plan, Modeling Quick Plan, Construction of Prototype, and Deployment. The result of the research is a web-based Yobagi application that functions well, as evidenced by functional testing using the Blackbox method. Furthermore, the Responsive Web Design feature on the Yobagi system was also tested to test the performance of the features on several different types of smartphones.